Let's open our eyes to the importance of vaginal microbiota. Correlation between dysbiosis and HPV infection: A review - Patrycja Kostrzewa; Michał Kostrzewa; Maciej Sergiusz Anioł; Anna Palmerska; Andrzej Piela; Kinga Piela; Olga Katarzyna Przybyła; Anna Szurma; Rafał Szurma; Szymon Pacek (Kazimierz Wielki University, 2024)
Infections with the human papillomavirus (HPV) are one of the most common sexually transmitted diseases and are the main cause of precancerous changes and cervical cancer development. However, mere infection does not guarantee the development of disease or carcinogenesis. For this to occur, high-risk types of HPV must integrate into the host cell genome, transitioning into a persistent form of infection. Following the discovery of risk factors for HPV infection and factors predisposing infection to a persistent form, the number of studies investigating the correlation between vaginal dysbiosis and infection has significantly increased. Numerous studies document a significant association between the state of vaginal bacterial flora and HPV infection, leading to the development of plentiful studies on infection pathogenesis, risk factors, prevention, and treatment methods using bacteria. In this paper, based on recently published studies and current state of science knowledge, we will outline the topic of vaginal microbiome, emphasize the importance of bacteria inhabiting the vagina for human health, and identify the problem of changes in vaginal microflora. We would like to contribute to the dissemination of knowledge about the vaginal microbiome and general knowledge about taking care of its health. We will also summarize available treatment methods based on bacterial environment and discuss those methods for which research is currently underway or should be initiated.